The compliance with the 2011 standards of selected secondary school library media centers in Antipolo City - Santillan, Kevin Bryan O.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study gathered information to determine the compliance of the selected school libraries in Antipolo City to the following sections of the 2011 Standards for Philippine Libraries for School Library Media Centers: (1) Mission, Goals, and Objectives, (2) Administration, (3) Human Resources, (4) Collection Management, (5) Services and Utilization, (6) Physical Facilities, (7) Financial Resources, and (8) Linkages and Networking. The respondents of the study were composed of head librarians and principals from () La Salle College Antipolo, (2) Nazareth Christian School, (3) The Pleasant Mount School and (4) College of San Benildo - Rizal only.
Aside from the questionnaire, the researcher interviewed the respondents for further information. The researcher also visited the libraries to determine whether the furniture and equipment specifications have been complied with the selected schools. Document analysis was done to determine the extent of compliance of the said schools in terms of acquisitions, policies, etc.
School A has not complied with most of the 2011 Standards. The school was not aware of any library standards whether it is the 1998 Guidelines of the 2011 Standards. In addition, the school's biggest challenge is the finances since the school collects minimal amount of library fee.
School B has complied with most of the 2011 Standards, because the school has enough funds for their library improvement. The school also has applied for PAASCU accreditation and the accreditation became a reason for the school to improve the library.
School C has not complied with most of the 2011 Standards, because the school was not aware of any library standards whether it is the 1998 Guidelines or the 2011 Standards.
In addition, the owners of School C are not so supportive in library decision making because they think that the library is just a requirement for a school and not a necessity. School B has complied with most of the 2011 Standards, because the school has enough funds for their library improvement. The school has applied for an accreditation of its sister school.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: School libraries -- Philippines -- Antipolo City -- Standards